1997
DOI: 10.1002/chem.19970030617
|View full text |Cite
|
Sign up to set email alerts
|

Towards 2‐Silaallenes: Synthesis of Spirocyclic Precursors

Abstract: Abstract:Reactions of dichlorodivinylsilane (2) and LitBu in a molar ratio 131 and 1/'2 lead to highly reactive intermediates, which can be trapped by suitable reagents. In the presence of trimethylmethoxysilane, norbornadiene, anthracene and diphenylacetylene, products are formed that provide evidence for the intermediate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…al reported that trisilacyclosilylidene (14) is by only 2.7 kcal/mol with ZPE correction higher in energy than to trisilaallene (11), which has quite similar geometry to that of 14 at B3LYP/6-31G(d,p) [19]. Likewise, we have determined that 14 is by 2.7, 2.8, 4.4, 5.8, and 6.4 kcal/mol with ZPE correction, higher in energy than 11 at the B3LYP/6-31G(d), B3LYP/6-31 þ G(d,p), B3LYP/ cc-pVTZ, MP2/6-31G(d), and MP2/6-31 þ G(d,p) levels, respectively.…”
Section: Rearrangement Of Free Silacyclopropylinedes To Silaallenesmentioning
confidence: 97%
See 3 more Smart Citations
“…al reported that trisilacyclosilylidene (14) is by only 2.7 kcal/mol with ZPE correction higher in energy than to trisilaallene (11), which has quite similar geometry to that of 14 at B3LYP/6-31G(d,p) [19]. Likewise, we have determined that 14 is by 2.7, 2.8, 4.4, 5.8, and 6.4 kcal/mol with ZPE correction, higher in energy than 11 at the B3LYP/6-31G(d), B3LYP/6-31 þ G(d,p), B3LYP/ cc-pVTZ, MP2/6-31G(d), and MP2/6-31 þ G(d,p) levels, respectively.…”
Section: Rearrangement Of Free Silacyclopropylinedes To Silaallenesmentioning
confidence: 97%
“…Veszpremi et al also indicated that one of four possible structural isomers at the Si 3 H 4 potential surface, 11, is the highly bent silylene [14]. Therefore, we carried out various theoretical calculations for the bent structure (11), which is dramatically different from those of the carbon analogue, H 2 C]C]CH 2 , and from 1-silaallenes [18,19]. The most unusual geometrical feature of trisilaallene is its very extreme SiSiSi bond angle of 69.4 at the B3LYP/6-31G(d) level (Fig.…”
Section: Rearrangement Of Free Silacyclopropylinedes To Silaallenesmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the fact that 2-silaallene (CH 3 ) 3 CH 2 CH=Si= CHCH 2 C(CH 3 ) 3 (221) was active in cycloaddition to N, no formation of the corresponding cycloadduct was not observed in the reaction with Q [111].…”
Section: Silenesmentioning
confidence: 53%